Weightlifting for sports performance - Brewer, C.; Favre, M. (Strength and conditioning for sports performance, 2016)
Chapter 11 highlighted the importance of force production capacities to human performance, and identified key elements of force production that should be the focus of a resistance training programme. This chapter looks at the practical application of this work, with particular reference to the role of weightlifting movements in an effective strength and conditioning (S&C) programme. Resistance training (also called strength training) refers to a specialised method of conditioning whereby an individual is working against a wide range of resistive loads with modes including the use of body weight, weight and pneumatic resistance machines, free weights (barbells, dumbbells and kettlebells), elastic bands and medicine balls. Weightlifting on the other hand is a sport, which involves the performance of the snatch and clean and jerk lifts in competition [24]. Increasingly, weightlifting movements and their derivatives are being utilised in the training of athletes other than weightlifters, owing to their inherent advantages in developing key physical capacities required for optimal performance in a range of sports. The UK Strength and Conditioning Association (UKSCA) accreditation process selects three key exercises that can be differentially used to develop high-force and/or high-velocity qualities in the athlete (therefore enabling the athlete to transfer the training benefits to sports performance through the ability to generate impulse). These are the squat, the clean and the snatch. These movements, and their derivatives, are explored in detail within this chapter. The coaching points associated with each lift are based on extensive research and with the major papers contributing to this listed in the references and further reading section at the end of the chapter.